Carbazole Alkaloids from Stem Bark of Murraya koenigii (L.) Spreng - Sumayya Saied; Farkhanda Hassan; Shaista Naz; Humaira Siddiqi (Journal of Basic & Applied Sciences, 2015)
Murraya koenigii (L.) Spreng(curry patta) has different therapeutic uses and rich source of carbazole alkaloids. Phytochemical studies on the stem bark of M. koenigii yielded one new carbazole alkaloid, afifine, along with two known carbazole alkaloids, mahinimbine and girinimbine. These compounds were isolated using chromatographic methods and identified using spectroscopic techniques.